Dominant groups of technical activities of players at all playing positions prior to a successful field shot on the European Championship "Poland 2009" - Badza, V.; Marinkovic, D. (2nd International scientific conference: Exercise and quality of life, Novi Sad. March 24/26th 2011, 2011)
Basketball requires the training process with more appropriate methods and techniques, and it is necessary to analyze the basketball game in terms of competition. The aim of this research is to diagnose the dominant group of technical-tactical activities that players applied at different playing positions before they scored points from field goal area, at the European Championship, "Poland 2009". The study included the total of 23 matches from different levels of competition, and 168 players. All 45 activities were classified in four groups. The criteria for the grouping activities were methods of shooting and shooting place. The data were statistically processed and analyzed. The results of the above analysis show that the parameters are different on each playing position.